Laparoscopic Pyloromyotomy: A Study of the Learning Curve - Binet, Aurélien; Bastard, François; Meignan, Pierre; Braïk, Karim; Le Touze, Anne; Villemagne, Thierry; Morel, Baptiste; Robert, Michel; Klipfel, Clémence; Lardy, Hubert (European Journal of Pediatric Surgery, 2018)
Introduction Laparoscopic pyloromyotomy (LPM) is a minimally invasive surgical technique used in pyloric stenosis treatment. This technique is safe, effective, and does not show more complications than laparotomy. Nevertheless, this technique requires an acquisition period to be optimally applied. This study analyses the learning curve of LPM.Materials and Methods Seven surgeons were retrospectively evaluated on their 40 first LPM. Patient data were recorded, including peroperative data (operation length and complications) and postoperative recoveries (renutrition, vomiting, and complications). The learning curves were evaluated and each variable was compared with the different moments of the learning curve.Results The mean operative time is 25 ± 11 minutes. It significantly decreases with the learning curve (p < 0.01). Ten procedures were necessary to acquire the operative technics. However, postoperative complications with a necessary redo procedure appear after the 10th patient. There is no significant difference concerning long-term postoperative complications according to the learning curve and to surgeons. The best results are recorded after the 20th patients. Hospital length of stay also decreases significantly after the 10th procedure. The recorded postoperative vomiting is independent to the operative time as the ad libitum feedings recovery.Conclusion The learning curve of LPM is cut into three stages. Only 10 cases are needed to acquire the gesture. Complications appear after this acquirement period.
Keywords: hypertrophic pyloric stenosis; laparoscopy; learning curve; pediatric surgery